MOTIVASI SISWA DALAM PEMBELAJARAN SENI TARI DI SMP N 3 PADANG - Pratiwi, Soraya Ayu; Iriani, Zora; Astuti, Fuji (FBS Universitas Negeri Padang, 2019)
AbstractThis study aimed to describe the motivation of students to take part in learning dance in SMP N 3 Padang. This type of research was qualitative research with descriptive analysis method. The main instrument in this study was the researcher selves and assisted with supporting instruments such as stationery and cameras. The types of data used are primary data and secondary data. Techniques of data collection were carried out by observation, interviews and documentation. The results of data collection are presented, concluded and verified to obtain the correct data conclusions. The results showed that students' motivation in dance learning at SMPN 3 Padang was caused by individual students’ factors and teacher factors, with a poor percentage result, because the teachers in the learning process did not use varied methods and media. In the learning process, the teacher does not use media (laptops, pictures, videos, infocus, tape / speakers) as a tool. The teacher only explains the subject matter. From the results of observations and interviews, students' motivation looks less motivated caused by individual factors and teacher factors.Keywords: motivation, learning the art of dance